AJARAN BERPERILAKU YANG BENAR DALAM SERAT RAREPE WONG NGAWULA - mirya anggrahini nimpuno (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2012)
The study entitled “ The Virtues of The Right Behaviour in Serat Rarepe Wong Ngawula ” is based on the thought that Serat Rarepe Wong Ngawula is considered as one of our ancestor’s heritage of written culture containing the right behaviour in human life. This virtues are very important for both people of the past and those who live in present time. Therefore, a scientificstudy is needed in order to reveal the messages of the manuscript for the Indonesian people, especially the Javanese people.Key words : Serat Rarepe Wong Ngawula, the virtues of the right behaviour, ancestor’s heritage, javanese.